Lost in Translation: Defects in Transfer RNA Modifications and Neurological Disorders - Bednářová, Andrea; Hanna, Marley; Durham, Isabella; VanCleave, Tara; England, Alexis; Chaudhuri, Anathbandhu; Krishnan, Natraj (Frontiers in Molecular Neuroscience, 2017)
Transfer RNAs (tRNAs) are key molecules participating in protein synthesis. To augment their functionality they undergo extensive post-transcriptional modifications and, as such, are subject to regulation at multiple levels including transcription, transcript processing, localization and ribonucleoside base modification. Post-transcriptional enzyme-catalyzed modification of tRNA occurs at a number of base and sugar positions and influences specific anticodon - codon interactions and regulates translation, its efficiency and fidelity. This phenomenon of nucleoside modification is most remarkable and results in a rich structural diversity of tRNA of which over 100 modified nucleosides have been characterized. Such hypermodified nucleosides, are found most often in the wobble position of tRNAs, which play a direct role in maintaining translational efficiency and fidelity, codon recognition etc. Several recent studies have pointed to a link between defects in tRNA modifications and human diseases including neurological disorders. Therefore, defects in tRNA modifications in humans need intensive characterization at the enzymatic and mechanistic level to pave the way to understand how lack of such modifications are associated with neurological disorders with the ultimate goal of gaining insights into therapeutic interventions.